Technical Project Management in Living and Geometric Order - Russell, Jeffrey; Pferdehirt, Wayne; Nelson, John (Open textbook library., 2018)
The Technical Project Management class is designed to help students build on their past experiences and develop effective strategies for managing complex technical projects, with an emphasis on applying project management concepts to real-world problems. In the weekly web conferences, the class comes together in community to discuss the lesson topics, considering the practical applications of the concepts in each subject area.